Changes in Expression of Key Genes in Ceca of Chicken Broilers as Affected by Glyphosate, Antibiotics and a Coccidiostat - Georgi Y. Laptev; Daria G. Turina; Vitali Y. Morozov; Elena A. Yildirim; Elena P. Gorfunkel; Larisa A. Ilina; Valentina A. Filippova; Evgeni A. Brazhnik; Natalia I. Novikova; Veronika K. Melikidi; Kseniya A. Sokolova; Ekaterina S. Ponomareva; et al. (Animals)
Studies have shown the presence of residual amounts of the herbicide glyphosate in poultry feed, which leads to its bioaccumulation in the body. Recently, it has been established that exposure to low levels of glyphosate over a long period may have serious negative effects on poultry health. Moreover, combined exposure to several toxicants can potentially lead to additive and/or synergistic effects. The purpose of this study was to analyze changes in meat productivity and the expression dynamics of key genes (IGF1, IGF2, MYOG, MYOZ2, SLC2A1, SLC2A2, MSTN, MUC2, OCLN, CLDN1, TLR2, TLR4, CAT, SOD1, PRDX6, and HMOX1) in the cecum of broilers as affected by glyphosate, antibiotics and a coccidiostat (anticoccidial drug). Day-old Ross 308 broiler chickens (n = 260) were divided into four groups, including a control group (CONT) fed the basic diet (BD), and three experimental groups: GLY (BD + glyphosate), GLY+ANT (BD + glyphosate and antibiotics enrofloxacin and colistin methanesulfonate), and GLY+CS (BD + glyphosate and the coccidiostat ammonium maduramycin). Samples were collected at control 7, 14, and 40 days of rearing, 50 mg each from three birds from each group. The mean body weight in each group was determined after the individual weighing of the entire flock. At 7 days of age, an upregulating effect on the expression of the immune-related TLR2 gene was detected in Groups GLY+ANT and GLY+CS compared to Group CONT (p = 0.044 and p = 0.042, respectively) and Group GLY (p = 0.049 and p = 0.044, respectively). At 40 days of age, this gene expression, conversely, decreased in Groups GLY+ANT and GLY+CS compared to Group CONT (p = 0.041 and p = 0.038, respectively). Glyphosate (Group GLY) upregulated the mRNA level of genes associated with productivity (IGF1, IGF2, and MSTN) at 7 days of age by 3.7 times (p = 0.041, p = 0.036 and p = 0.039, respectively) and, conversely, decreased it at a later age (14 and 40 days) compared to Group CONT (p = 0.024, p = 0.049 and p = 0.047, respectively, at 14 days, and p = 0.037 and p = 0.036 and p = 0.035, respectively, at 40 days of age). Thus, we identified detrimental changes in the expression of key broiler genes as influenced by glyphosate, as well as its combinations with antibiotics and a coccidiostat, which may have negative consequences for the poultry industry.